A comparative study of RNA yields from museum specimens, including an optimized protocol for extracting RNA from formalin-fixed specimens - Speer, Kelly A.; Hawkins, Melissa T. R.; Flores, Mary Faith C.; McGowen, Michael R.; Fleischer, Robert C.; Maldonado, Jesús E.; Campana, Michael G.; Muletz-Wolz, Carly R. (Frontiers in Ecology and Evolution, 2022)
Animal specimens in natural history collections are invaluable resources in examining the historical context of pathogen dynamics in wildlife and spillovers to humans. For example, natural history specimens may reveal new associations between bat species and coronaviruses. However, RNA viruses are difficult to study in historical specimens because protocols for extracting RNA from these specimens have not been optimized. Advances have been made in our ability to recover nucleic acids from formalin-fixed paraffin-embedded samples (FFPE) commonly used in human clinical studies, yet other types of formalin preserved samples have received less attention. Here, we optimize the recovery of RNA from formalin-fixed ethanol-preserved museum specimens in order to improve the usability of these specimens in surveys for zoonotic diseases. We provide RNA quality and quantity measures for replicate tissues subsamples of 22 bat specimens from five bat genera (Rhinolophus, Hipposideros, Megareops, Cynopterus and Nyctalus) collected in China and Myanmar from 1886 to 2003. As tissues from a single bat specimen were preserved in a variety of ways, including formalin-fixed (8 bats), ethanol-preserved and frozen (13 bats), and flash frozen (2 bats), we were able to compare RNA quality and yield across different preservation methods. RNA extracted from historical museum specimens is highly fragmented, but usable for short-read sequencing and targeted amplification. Incubation of formalin-fixed samples with Proteinase-K following thorough homogenization improves RNA yield. This optimized protocol extends the types of data that can be derived from existing museum specimens and facilitates future examinations of host and pathogen RNA from specimens.